PEMENUHAN HAK ANAK SEBAGAI TERSANGKA DALAM PENYIDIKAN TINDAK PIDANA KECELAKAAN LALU LINTAS - Afrino, Afrino (Universitas Ekasakti, 2019)
Lately, there have been frequent traffic accidents which have caused many losses. The Sijunjung Regional Police Laka Satlantas Unit has handled 35 cases of traffic accident committed by children, so far it has always prioritized child protection in examining children who are dealing with the field of law. This research is a descriptive analytical study. Adapaun the results of the implementation of the implementation of the fulfillment of children's rights as suspects in the investigation process, can be seen from careful actions carried out by investigators, meaning that if the cases carried out by children are still classified as minor acts, there should be no detention measures, whereas if the case is a criminal offense detention can be carried out, in the investigation process the suspect must be accompanied by his parents even though his legal advisor does not come to accompany the suspect. BAPAS in the inspection phase is obliged to assist the suspect. Examination of child suspects, it should be noted that there is a special room that is comfortable and friendly for child offenders, and the Diversion process is prioritized to achieve the best interests for children. Constraints encountered by the police in fulfilling children's rights as suspects in the process of investigating traffic accident crimes, namely in the process of investigating and detaining suspected children, where there are internal factors, namely members of Unit Laka personnel who are few in number, BAPAS sometimes unable to attend, legal counsel sometimes unable to attend. Efforts to overcome the obstacles that arise in the provision of children's rights as suspects in the investigation process of traffic accident crimes, where the Sijunjung Regional Police have dealt with these obstacles in accordance with what is needed, among others asking for funds to add detention rooms, writing BAPAS and legal counsel, and providing socialization to schools or to the community regarding enforcement of traffic laws in general and the protection of children in particular.